2013
DOI: 10.1371/journal.pone.0078587
|View full text |Cite
|
Sign up to set email alerts
|

Solution Scattering and FRET Studies on Nucleosomes Reveal DNA Unwrapping Effects of H3 and H4 Tail Removal

Abstract: Using a combination of small-angle X-ray scattering (SAXS) and fluorescence resonance energy transfer (FRET) measurements we have determined the role of the H3 and H4 histone tails, independently, in stabilizing the nucleosome DNA terminal ends from unwrapping from the nucleosome core. We have performed solution scattering experiments on recombinant wild-type, H3 and H4 tail-removed mutants and fit all scattering data with predictions from PDB models and compared these experiments to complementary DNA-end FRET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 43 publications
6
40
0
Order By: Relevance
“…This conclusion was also supported by dynamic light scattering investigations, which displayed a larger hydrodynamic diameter for Telo-NCP in comparison with 601-NCP (data not shown). Earlier works have shown that the depth of the dip in the NCP SAXS spectrum at 0.14 Å -1 is sensitive to DNA unwrapping (71)(72)(73)(74). The NCP at low concentration (1-2.5 mg/mL) in low salt buffer (10 mM KCl) exhibit minimal inter-particle interactions, thereby facilitating the study of the form factor of the NCP SAXS spectrum (52).…”
Section: The Telo-ncp Exhibits a Stable Yet Dynamic Structure In Solumentioning
confidence: 99%
“…This conclusion was also supported by dynamic light scattering investigations, which displayed a larger hydrodynamic diameter for Telo-NCP in comparison with 601-NCP (data not shown). Earlier works have shown that the depth of the dip in the NCP SAXS spectrum at 0.14 Å -1 is sensitive to DNA unwrapping (71)(72)(73)(74). The NCP at low concentration (1-2.5 mg/mL) in low salt buffer (10 mM KCl) exhibit minimal inter-particle interactions, thereby facilitating the study of the form factor of the NCP SAXS spectrum (52).…”
Section: The Telo-ncp Exhibits a Stable Yet Dynamic Structure In Solumentioning
confidence: 99%
“…Although fluorescence of DNA and nucleosome with acceptor (A 41st or A 27th) is similar (Figure S12, Supporting Information), nucleosome containing donor (D 40th) increased fluorescence intensity 1.89‐fold compared with duplex DNA. We estimated R DA based on a minimized structure using the software BIOVIA discovery studio version 17.1 . After minimization of th dG and tC‐containing nucleosome structure, the R DA of nucleosome with D 40th+A 41st (47.2±0.06 Å) and D 40th+A 27th (26.5±0.05 Å) was observed (Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We estimated R DA based on am inimized structure using the softwareB IOVIA discoverys tudio version 17.1. [25][26][27][28][29][30][31] After minimizationo f th dG and tC-containing nucleosome structure, the In the B-form structure,t he angle between the helicala xis and the fluorescent nucleobase is almost 908 in the cylinder model of the DNA duplex because of the fixed parallel plan of the fluorescent nucleobase caused by hydrogen bonding with the counterbase and stacking interaction between neighboring bases, indicating that k 2 can be assumed to between 0a nd 1. [20,41,42] On the other hand, the base pair of the DNA duplex in the nucleosome undergoes geometrical changes such as roll, tilt, and twist unlike typical B-form DNA.…”
Section: Resultsmentioning
confidence: 99%
“…We chose these examples because they correspond to two areas of active investigation, DNA breathing and unwrapping from a NCP, and the configuration of a short array of nucleosomes. [10– For the NCP, we designated 30 bp on each end to be flexible (in Figs.…”
Section: Examplesmentioning
confidence: 99%
“…While much has been learned by studying NCPs and nucleosome arrays in these biologically artificial environments, understanding the structure–function relationship of chromatin in vivo requires experiments in solution. To date, efforts to identify model structures from solution studies of nucleosomes and nucleosome arrays have been limited to qualitative comparisons, or structure models generated from dummy spheres, manual modifications of atomic structures, or by replacing nucleosome‐bound DNA with linear DNA fragments . Robust structure models of these and other nucleosome complexes require efficient simulation tools to complement the experimental methods used; in this context, a robust structure model refers to an atomic representation of a physically realistic molecular structure.…”
Section: Introductionmentioning
confidence: 99%